Enhanced delivery of liposomes to lung tumor through targeting interleukin-4 receptor on both tumor cells and tumor endothelial cells - Chi, Lianhua; Na, Moon-Hee; Jung, Hyun-Kyung; Vadevoo, Sri Murugan Poongkavithai; Kim, Cheong-Wun; Padmanaban, Guruprasath; Park, Tae-In; Park, Jae-Yong; Hwang, Ilseon; Park, Keon Uk; Liang, Frank; Lu, Maggie; et al. (ELSEVIER SCIENCE BV, 2015)
A growing body of evidence suggests that pathological lesions express tissue-specific molecular targets or bio-markers within the tissue. Interleukin-4 receptor (IL-4R) is overexpressed in many types of cancer cells, including lung cancer. Here we investigated the properties of IL-4R-binding peptide-1 (IL4RPep-1), a CRKRLDRNC peptide, and its ability to target the delivery of liposomes to lung tumor. IL4RPep-1 preferentially bound to H226 lung tumor cells which express higher levers of IL-4R compared to H460 lung tumor cells which express less IL-4R. Mutational analysis revealed that C1, R2, and R4 residues of IL4RPep-1 were the key binding determinants. IL4RPep-1-labeled liposomes containing doxorubicin were more efficiently internalized in H226 cells and effectively delivered doxorubicin into the cells compared to unlabeled liposomes. In vivo fluorescence imaging of nude mice subcutaneously xenotransplanted with H226 tumor cells indicated that IL4RPep-1-labeled liposomes accumulate more efficiently in the tumor and inhibit tumor growth more effectively compared to unlabeled liposomes. Interestingly, expression of IL-4R was high in vascular endothelial cells of tumor, while little was detected in vascular endothelial cells of control organs including the liver. IL-4R expression in cultured human vascular endothelial cells was also up-regulated when activated by a pro-inflammatory cytokine tumor necrosis factor-a. Moreover, the up-regulation of IL-4R expression was observed in primary human lung cancer tissues. These results indicate that IL-4R-targeting nanocarriers may be a useful strategy to enhance drug delivery through the recognition of IL-4R in both tumor cells and tumor endothelial cells. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ALPHA-CHAIN; CYTOTOXIN THERAPY; EGFR MUTATION; CANCER CELLS; 1ST-LINE TREATMENT; OXIDATIVE STRESS; DRUG-DELIVERY; PHAGE DISPLAY; OPEN-LABEL; IN-VIVO